The role of risk and crisis management in achieving development in the tourism sector - Tawfick, Ibrahim Hassan; Saddiq, Mohamed Fathy; Salem, Bahlol Ahmed (Journal of Risk and Crisis Management, 2024)
Tourism institutions and bodies operate in a climate characterized by movement, change, and cultural and technological diversity. The tourism sector is one of the sectors most affected by global stability and peace. Therefore, it is exposed to many complex risks and crises internally and externally, and they have their causes and consequences that vary from one country to another, from one region to another, and from one organization to another depending on The nature and specificity of its work, whether it is (a hotel, a company, airlines, entertainment facilities, etc.), and it must face all kinds of risks, whether these risks are tourism, economic, political, security, or other, through a well-thought-out, scientific plan to manage risks and crises so that There is always a need to develop with the level of those problems that it faces in order to maintain the elements of available and future demand and supply in different countries and to contribute positively to solving these problems through administrative thought that is appropriate to the type of problem or crisis through the availability of all the elements of successful dealing with these risks and crises for the industry tourism.